2015
DOI: 10.1371/journal.pone.0123871
|View full text |Cite
|
Sign up to set email alerts
|

Reading Mammal Diversity from Flies: The Persistence Period of Amplifiable Mammal mtDNA in Blowfly Guts (Chrysomya megacephala) and a New DNA Mini-Barcode Target

Abstract: Most tropical mammal species are threatened or data-deficient. Data collection is impeded by the traditional monitoring approaches which can be laborious, expensive and struggle to detect cryptic diversity. Monitoring approaches using mammal DNA derived from invertebrates are emerging as cost- and time-effective alternatives. As a step towards development of blowfly-derived DNA as an effective method for mammal monitoring in the biodiversity hotspot of Peninsular Malaysia, our objectives were (i) to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(69 citation statements)
references
References 50 publications
(75 reference statements)
0
57
0
Order By: Relevance
“…This may limit the detections to species with higher primer binding affinity, resulting in species diversity being underrepresented (Shokralla et al 2012). Lee et al (2015) found the primers used in this study exhibited no strong amplification bias across mammal species (from Peninsular Malaysia), but the test only included a limited number of species (n = 41).…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…This may limit the detections to species with higher primer binding affinity, resulting in species diversity being underrepresented (Shokralla et al 2012). Lee et al (2015) found the primers used in this study exhibited no strong amplification bias across mammal species (from Peninsular Malaysia), but the test only included a limited number of species (n = 41).…”
Section: Discussionmentioning
confidence: 88%
“…Ten blowfly traps baited with rotten fish (see Lee et al 2015) were set per transect at 10 m intervals and 2 m above the ground. The traps were emptied every 24 h, and collected blowflies (Diptera: Calliphoridae) were frozen at -20°C within 5 h of trap emptying.…”
Section: Baited Blowfly Trapsmentioning
confidence: 99%
See 3 more Smart Citations